Knowledge and Practice of Diabetic Patients Attending Diabetic Clinic about Oral Health and Foot Care – Albyda, 2017 - Greiw, Azza; Ayyad, Halima (Libyan Journal of Dentistry, 2018)
Background: According to the International Diabetes Federation (IDF), more than 34.6 million people in the MiddleEast and North Africa Regions have diabetes. In Libya 2009 according to stepwise prevalence of diabetes was 16.4%.It is well-established that diabetes increases the prevalence, severity, and progression of oral diseases as well as foot ulcers. The role of health professional is very important in improving the knowledge and practices regarding oralhealth and foot care. Knowledge and awareness of Jordanian and Emirates diabetics were low about oral health. The aim of our study was to determine diabetic patients’ level of knowledge, awareness and practice about oral health and foot care. Subjects and methods; All diabetic cases attended AL-Bayda diabetic clinic during the year 2017 were included in the study. Cross section study design was applied using a structured questionnaire which included data related to personal characteristics and assessment of KAP of participants. Results: The highest proportion of cases (53.2%) their age ranged from 50-59 years. Nearly 59% were females and 41% were males. The mean duration of DM was 13.19± 7.92 years. Knowledge of participants about oral complication was low compared to systemic complication. Less than half of diabetic cases brushed their teeth, and eighteen percent used tooth floss. Only two percent of diabetics received their knowledge about diabetes from dentists. Recommendation There is a need that all health professional including dentists should play an important role in educating diabetics about diabetes and related complications.